Respiratory symptoms and ventilatory function tests in Nigerians with HIV infection - Onyedum, CC (Makerere Medical School, 2010)
BACKGROUND: The impact of the human immunodeficiency virus (HIV) infection on the respiratory system of Africans has been little studied. This study aimed to determine the pattern of respiratory symptoms and ventilatory functions in HIV infected Nigerians. METHODS: In this cross sectional study, Respiratory symptoms frequency, Forced vital capacity (FVC), Forced expiratory volume in one second (FEV(1)), FEV(1)/FVC ratio, Forced expiratory flow between 25% and 75% of FVC, were determined in 100 HIV positive subjects and compared with values in 100 HIV negative controls. RESULTS: HIV positive patients had significantly more respiratory symptoms and lower ventilatory function tests values compared to the matched controls (p<0.05). HIV patients with at least one respiratory symptom and those with CD4 count less than 200cells/µl had lower ventilatory function values than their counterparts. 32% of the HIV patients had restrictive ventilatory functional impairment. (p<0.05). Using regression analysis, factors like HIV status, CD4 count and presence of respiratory symptoms were found to be associated with impairment in ventilatory functions. CONCLUSIONS: HIV infected patients had more frequent respiratory symptoms and lower ventilatory function values. Further lung function studies and CT scanning in HIV positive patients especially in those with respiratory symptoms are indicated.